2009
DOI: 10.1016/j.taap.2009.02.015
|View full text |Cite
|
Sign up to set email alerts
|

2-(4-Amino-3-methylphenyl)-5-fluorobenzothiazole is a ligand and shows species-specific partial agonism of the aryl hydrocarbon receptor

Abstract: Non-standard abbreviations.2-(4-amino-3-methylphenyl)-5-fluorobenzothiazole, 5F 203; tetrachloroazoxybenzene, TCAOB; 2,3,7,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In the related context of pharmacological interactions, Bazzi et al, identified a possible mechanism of action for the antiproliferative effect of phenylbenzothiazoles, which can be attributed to CYP1 family-mediated metabolism [66]. They suggested that the AhR signaling pathway may be involved in mediating the anticancer activity of novel 2-(4-aminophenyl) benzothiazole drugs in MCF-7 breast cancer cells.…”
Section: A Pharmacological Interactions Between Phenylbenzothiazolementioning
confidence: 99%
“…In the related context of pharmacological interactions, Bazzi et al, identified a possible mechanism of action for the antiproliferative effect of phenylbenzothiazoles, which can be attributed to CYP1 family-mediated metabolism [66]. They suggested that the AhR signaling pathway may be involved in mediating the anticancer activity of novel 2-(4-aminophenyl) benzothiazole drugs in MCF-7 breast cancer cells.…”
Section: A Pharmacological Interactions Between Phenylbenzothiazolementioning
confidence: 99%
“…Thus, the spectrum of activity of this bis-methyl ether extends to human cell lines derived from intractable colorectal carcinomas (CRC). A potent AhR ligand (K i ¼ 6.8 nmol/L), GW-610 is sequestered exclusively and rapidly by sensitive breast and CRC cells only (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The statistical results are derived from one-way ANOVA/Tukey's multiple range tests. treatment periods increase the risk of chemical metabolism, and may affect potency estimates (Bazzi et al, 2009;DeGroot et al, 2015). In this case, we propose that BDE-99 is a transient Ahr agonist.…”
Section: Discussionmentioning
confidence: 95%